Faktor Penyebab Kurangnya Minat Anak Keluarga Nelayan Melanjutkan Pendidikan ke Perguruan Tinggi di Desa Puger Kulon Kecamatan Puger - Wijaya, Shendy Andrie; Susilo, David K; Sari, Devi Septiani Ratna (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This study aims to describe the causative and dominant factors causing the lack of interest in fisher family children to continue their education to higher education in Puger Kulon Village, Puger District. This research is a descriptive qualitative research. The number of informants was 6 people, the selection of informants in this study used a purposive sampling technique, with the criteria of fishermen family children who did not continue their education to college as the main informants and the parents of the children concerned as supporting informants. The data collection techniques used were observation, interview and documentation. Data analysis in this study used data reduction, data presentation and drawing conclusions. Data validation techniques use source triangulation and techniques. The results showed that: the factors causing the lack of interest in the children of fishermen's families to continue their education to higher education in Puger Kulon Village, Puger District were the child's own desires, family economic factors, no encouragement from parents, location factors, and environmental factors. Meanwhile, the dominant factor causing the lack of interest in children